Customer satisfaction on service quality dimensions - K, BHASKAR; P, SUBRAMANYAM (Journal of Management and Science, 2021)
The purpose of this paper is to empirically investigate the influence of dimensions of service quality towards satisfaction in the context of Indian retail market. The paper focused to examine the relationship between satisfaction and service quality dimensions. A study has been conducted on 20 supermarkets in Kadapa district, A.P. India. The results of this research indicate that retail service quality positively influences satisfaction and trust. It is found that satisfaction also positively influences trust and loyalty. Satisfaction and trust mediate the relationship between retail service quality and loyalty on customer satisfaction.